Preparedness to Face the COVID-19 Pandemic in Hospice and Palliative Care Services in the Asia-Pacific Region: A Rapid Online Survey. (July 2021) - Lin, Cheng-Pei; Boufkhed, Sabah; Kizawa, Yoshiyuki; Mori, Masanori; Hamzah, Ednin; Aggarwal, Ghauri; Namisango, Eve; Higginson, Irene J.; Goh, Cynthia; Harding, Richard
Background: Hospice and palliative care services provision for COVID-19 patients is crucial to improve their life quality. There is limited evidence on COVID-19 preparedness of such services in the Asia-Pacific region. Aim: To evaluate the preparedness and capacity of hospice and palliative care services in the Asia-Pacific region to respond to the COVID-19 pandemic. Method: An online cross-sectional survey was developed based on methodology guidance. Asia-Pacific Hospice and Palliative Care Network subscribers (n = 1551) and organizational members (n = 185) were emailed. Descriptive analysis was undertaken. Results: Ninety-seven respondents completed the survey. Around half of services were hospital-based (n = 47, 48%), and public-funded (n = 46, 47%). Half of services reported to have confirmed cases (n = 47, 49%) and the majority of the confirmed cases were patients (n = 28, 61%). Staff perceived moderate risk of being infected by COVID-19 (median: 7/10). > 85% of respondents reported they had up-to-date contact list for staff and patients, one-third revealed challenges to keep record of relatives who visited the services (n = 30, 31%), and of patients visited in communities (n = 29, 30%). Majority of services (60%) obtained adequate resources for infection control except face mask. More than half had no guidance on Do Not Resuscitate orders (n = 59, 66%) or on bereavement care for family members (n = 44, 51%). Conclusion: Recommendations to strengthen the preparedness of palliative care services include: 1) improving the access to face mask; 2) acquiring stress management protocols for staff when unavailable; 3) reinforcing the contact tracing system for relatives and visits in the community and 4) developing guidance on patient and family care during patient's dying trajectory.